Maternal organophosphate flame‐retardant exposure alters offspring energy and glucose homeostasis in a sexually dimorphic manner in mice. Issue 4 (24th September 2020) - Walley, Sabrina N.; Krumm, Elizabeth A.; Yasrebi, Ali; Kwiecinski, Justine; Wright, Victoria; Baker, Chloe; Roepke, Troy A.
Abstract: Persistent organic pollutants such as organophosphate flame retardants (OPFRs) can accumulate in the body and interact with nuclear receptors that control energy homeostasis. One sensitive window of exposure is during development, either in utero or neonatal. Therefore, we investigated if maternal exposure to a mixture of OPFRs alters metabolism on a low‐fat diet (LFD) or a high‐fat diet (HFD) in both male and female offspring. Wild‐type C57Bl/6J dams were orally dosed with vehicle (sesame oil) or an OPFR mixture (1 mg/kg each of tris(1, 3‐dichloro‐2‐propyl)phosphate, triphenyl phosphate, and tricresyl phosphate) from gestation day 7 to postnatal day 14. After weaning, pups were fed LFD or HFD. To assess metabolism, we measured body weight and food intake weekly and determined body composition, metabolism, activity, and glucose homeostasis at 6 months of age. Although maternal OPFR exposure did not alter body weight or adiposity, OPFR exposure altered substrate utilization and energy expenditure depending on diet in both sexes. Systolic and diastolic blood pressure was increased by OPFR in male offspring. OPFR exposure interacted with HFD to increase fasting glucose in females and alter glucose and insulin tolerance in male offspring. Plasma leptin was reduced in male and female offspring when fed HFD, whereas liver expression of Pepck was increased in females and Esr1 (estrogen receptor α) was increased in both sex. The physiological implications indicate maternal exposure to OPFRs programs peripheral organs including the liver and adipose tissue, in a sex‐dependent manner, thus changing the response to an obesogenic diet and altering adult offspring energy homeostasis. Abstract : Maternal exposures to organophosphate flame retardants alter offspring metabolic and physiological process including changing how offspring utilize substrates for metabolic processes, increasing blood pressure and increasing glucose clearance in males, and altering metabolic hormone production.